2023
DOI: 10.3390/cancers15194693
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Novel Immunocompetent Mouse Cell Lines to Model Experimental Metastasis of High-Risk Neuroblastoma

Mayura R. Dhamdhere,
Dan V. Spiegelman,
Lisa Schneper
et al.

Abstract: NB, being a highly metastatic cancer, is one of the leading causes of cancer-related deaths in children. Increased disease recurrence and clinical resistance in patients with metastatic high-risk NBs (HR-NBs) result in poor outcomes and lower overall survival. However, the paucity of appropriate in vivo models for HR-NB metastasis has limited investigations into the underlying biology of HR-NB metastasis. This study was designed to address this limitation and develop suitable immunocompetent models for HR-NB m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Similarly, our recent findings demonstrated the effect of NB cell derived-EVs on fibroblasts using an in vitro system ( 15 ). We showed that treatments with EVs derived from our highly metastatic M1 (NB) cells ( 15 , 85 ) imparted invasive phenotype to the mouse fibroblasts, suggesting the EV-mediated CAF activation in NB, and a potential mechanism promoting NB metastasis.…”
Section: Role Of Evs In Nb Progressionmentioning
confidence: 87%
“…Similarly, our recent findings demonstrated the effect of NB cell derived-EVs on fibroblasts using an in vitro system ( 15 ). We showed that treatments with EVs derived from our highly metastatic M1 (NB) cells ( 15 , 85 ) imparted invasive phenotype to the mouse fibroblasts, suggesting the EV-mediated CAF activation in NB, and a potential mechanism promoting NB metastasis.…”
Section: Role Of Evs In Nb Progressionmentioning
confidence: 87%